Network pharmacology-based and experimental identification of the effects of Renshen Yangrong decoction on myocardial infarction - Zhao, Jiahao; Xu, Xing; Yang, Xiaolong (Frontiers in Pharmacology, 2022)
Objective: Myocardial infarction（MI）is one of the leading causes of death worldwide. Currently, the drugs used to treat MI have various side effects. Renshen Yangrong Decoction(RSYRD) plays a specific protective effect role in the treatment of cardiovascular diseases (CVD), with fewer side effects. However, there is no literature has reported the role of RSYRD in MI. In this study, network pharmacological analysis was combined with experiments in vivo and in vitro to validate the effects of RSYRD in the treatment of early stage of MI. Methods: Using a pharmacological network analysis strategy, we obtained the potential targets and signaling pathways of RSYRD acting on the early stage of MI. Then the protein-protein interaction (PPI) network was constructed, and the possible hub genes of RSYRD acting on MI were obtained. Finally, the therapeutic efficacy of RSYRD in treating MI was verified via experiments in vitro and in vivo. Results: RSYRD contained 56 bioactive components, 88 intersections between targets of RSYRD and MI, and 13 core genes were screened. KEGG and GO functional enrichment analysis predicted that RSYRD might play a therapeutic role in MI through oxidative stress, apoptosis and immune inflammatory signaling pathways. The results of experiments in vivo and in vitro revealed that in the early stage of MI, apoptosis of myocardial tissue, reactive oxide species (ROS) production, and levels of TNF-α and IL-6 were significantly increased. After RSYRD treatment, they significantly decreased. In terms of mechanisms, RSYRD could reduce ROS production to alleviate cell apoptosis. Conclusion: RSYRD can reduce cell apoptosis by lowering ROS production caused by hypoxia injury and improve cardiac function. RSYRD can also lower levels of TNF-α and IL-6 in the serum of mice.